The Right to Health Care Viewed from the Indigenous Research Paradigm: Violations of the Rights of an Aymara Warmi in Chile's Tarapacá Region - Adimelia Moscoso; Carlos Piñones-Rivera; Rodrigo Arancibia; Bárbara Quenaya (Harvard FXB Center for Health and Human Rights, 2023)
This paper reflects on the right to health care from the Indigenous research paradigm. We analyze the case of an Aymara wise warmi (woman) who died after the Chilean health care system failed to provide culturally appropriate care. In the wake of her death, our cooperative launched an interdisciplinary and collaborative research project in an effort to file an administrative complaint against the family health center that treated her. We explore the events surrounding her treatment and death, as well as the institutional written response. Our work elucidates the significant differences that exist between institutional and Indigenous perspectives on what constitutes a violation of the right to health care. We demonstrate that in order to establish the existence of such violations, Aymara people are compelled to develop evidence using a naturalistic scientific and legal framework that does not coincide with their ontology. Consequently, some events and violations are not legally recognized as culturally inappropriate health care unless they are viewed through an Indigenous lens. Finally, we reflect on the problem of evidence production, specifically regarding the right to health care. We argue that the fight for the right to health care can benefit from the Indigenous research paradigm-not only for the benefit of Indigenous people but also to provide culturally appropriate care to all people.